2020
DOI: 10.3389/fmolb.2020.00153
|View full text |Cite|
|
Sign up to set email alerts
|

Current Knowledge on the Function of α-Methyl Acyl-CoA Racemase in Human Diseases

Abstract: Branched chain fatty acids perform very important functions in human diet and drug metabolism. they cannot be metabolized in mitochondria and are instead processed and degraded in peroxisomes due to the presence of methyl groups on the carbon chains. Oxidative degradation pathways for lipids include α- and β-oxidation and several pathways. In all metabolic pathways, α-methyl acyl-CoA racemase (AMACR) plays an essential role by regulating the metabolism of lipids and drugs. AMACR regulates β-oxidation of branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…reported that AMACR has a diagnostic and prognostic value in glioblastoma ( 21 ). In PCa, AMACR can cause DNA damage that leads to the expression of peroxide, which promotes tumor progression ( 12 ). At present, many studies have pointed out that the AMACR mRNA level is significantly highly expressed in PCa tissues, and its sensitivity and specificity as a diagnostic marker are 82%–100% and 97%–100%, respectively ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that AMACR has a diagnostic and prognostic value in glioblastoma ( 21 ). In PCa, AMACR can cause DNA damage that leads to the expression of peroxide, which promotes tumor progression ( 12 ). At present, many studies have pointed out that the AMACR mRNA level is significantly highly expressed in PCa tissues, and its sensitivity and specificity as a diagnostic marker are 82%–100% and 97%–100%, respectively ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…AMACR (a-Methylacyl-CoA racemase, also known as P504S) is an enzyme that interconverts pristanoyl-CoA and C27-bile acyl CoA between their (R)- and (S)-stereoisomers ( 11 ). This protein is elevated in PCa tissue and can act as a biomarker of PCa ( 12 ). Urinary and circulating AMACR mRNA has been reported to perform well in PCa diagnosis ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The up-regulated circRNA_025332 may sponge for miRNA873-5p and increase the expression of AMACR, LAMP2, PLEKHA2, and CHD9, which was included in the metabolism of lipid pathway of the Reactome Gene Sets. The AMACR gene encodes an enzyme which regulates β-oxidation of branched chain lipids in peroxisomes and mitochondria and promotes chiral reversal of 2-methyl acids [25]. The LAMP2 gene encodes the lysosomal-associated membrane protein 2, which facilitates the transport of cholesterol [26].…”
Section: Discussionmentioning
confidence: 99%
“…It involves reversal of the 2 R ‐ to 2 S ‐fatty acyl‐CoA esters by the enzyme α‐methyl acyl‐CoA racemase 23 . This enzyme is also responsible for the inversion of ( R )‐ to ( S )‐ibuprofenoyl‐CoA ester 23 . α‐Methyl acyl‐CoA racemase was shown to be overexpressed in several cancers like glioblastoma and prostate cancer 24–26 .…”
Section: Introductionmentioning
confidence: 99%
“…Like other BCFAs, they cannot be metabolized in mitochondria but in peroxisomes. It involves reversal of the 2 R ‐ to 2 S ‐fatty acyl‐CoA esters by the enzyme α‐methyl acyl‐CoA racemase 23 . This enzyme is also responsible for the inversion of ( R )‐ to ( S )‐ibuprofenoyl‐CoA ester 23 .…”
Section: Introductionmentioning
confidence: 99%